Understanding Dynamics Dating Infidelity: Behaviors, Motivations, and Implications for Relationship Well-being - Aron Coffey Hartnett; Ziegler Leckie Croes; Beach Reynolds Hertlein; Sanner Kenrick Lasslo (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2023)
This research delves into the intricate dynamics of dating infidelity within the context of modern romantic relationships. By examining behaviors, motivations, consequences, challenges, and treatment interventions related to dating infidelity, this study offers a comprehensive exploration of this complex phenomenon. The findings reveal a spectrum of behaviors, ranging from emotional connections facilitated by technology to seeking sexual novelty and exploring relationships outside of primary partnerships. Motivational factors, including emotional fulfillment, sexual exploration, and dissatisfaction within the current relationship, emerge as key drivers of dating infidelity. The implications of infidelity extend beyond individuals, impacting relationship well-being and household welfare. Challenges such as communication breakdowns and unrealistic expectations hinder effective relationship dynamics. Treatment interventions, such as couples therapy, communication training, and strategies for rebuilding trust, provide a roadmap for addressing infidelity and promoting healing. This research enriches relationship science by offering insights into the evolving landscape of modern romantic connections and underscores the importance of open dialogue and communication to foster healthier and more resilient relationships.